Thermoregulation, hydration and performance over 6 days of trail running in the tropics - Hue, O.; Henri, S.; Baillot, M.; Sinnapah, S.; Uzel, A.-P. (International Journal of Sports Medicine, 2014)
The purpose of this study was to investigate thermal response, hydration and performance over a 6-day, 142-km trail running race in tropical conditions. 9 participants competed in the 2011 Gwadarun (30°C±2.4°C and 82±4% RH). Data were collected on days 1, 4 and 6. Gastrointestinal temperature (Tgi) and heart rate (HR) were measured using portable telemetry units, whereas blood samples were collected for hematocrit, osmolarity, plasma concentrations, alkaline reserves and creatine phosphokinase. The performances expressed in speed were correlated with both total body water and body mass loss per hour (TBWL.h-1 and DeltaBM.h-1), HR and changes in Tgi per hour (DeltaTgi.h-1): the more water and mass the participants lost, the higher the HR and the greater the Tgi change, and the better the performance. The Delta Tgi.h-1 was significantly correlated with DeltaBM.h-1, and the participants who lost the most mass had the greatest increases in Tgi. None of the blood parameters demonstrated significant changes. The present study showed that well-trained acclimated runners performing a 6-day trail race in a tropical environment and drinking ad libitum did not demonstrate heat-related illness or severe dehydration. Moreover, high performance was associated with increases in Tgi, TBW and BM losses per hour.